An Efficient Dynamic Authentication Scheme for Secure Network Coding - Ming He; Hong Wang; Lin Chen; Zhenghu Gong; Fan Dai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Network coding based applications are notoriously susceptible to malicious pollution attacks. Packets authentication schemes have been well-recognized as the most effective approach to address this security threat. However, existing packets authentication schemes for network coding either incur high computation overhead, or are vulnerable to arbitrary collusion among attackers. In this paper, we proposed a novel dynamic authentication scheme for secure network coding by dynamically using the linear vector subspaces of network coding. The scheme can efficiently detect packets generated by pollution attackers, and effectively resist arbitrary collusion among attackers. Our work is an innovative dynamic solution to frustrate pollution attacks with arbitrary collusion among attackers, and authentication cost can be further reduced by employing batch authentication in participating nodes. In addition, our scheme provides an efficient packet authentication without requiring the existence of any extra secure channel. Security analysis and simulations results demonstrate the practicality and efficiency of our scheme. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2470